Postoperative complications in patients subjected to drainage-free thyroidectomy. Hospital Central Universitario Dr. Antonio María Pineda (Boletin Médico de Postgrado, 2020)
In order to describe the postoperative complications in patients undergoing undrained thyroidectomy who attended the Servicio de Cirugía General of the Hospital Central Universitario Dr. Antonio María Pineda during the period January 2017-January 2018, a cross-sectional descriptive study was conducted through the review of 142 medical charts; patients has an average age of 50.23 ± 12.71 years with predominance of the female sex (88.03%) and normal nutritional status (58.45%). The preoperative diagnoses were conventional papillary carcinoma (49.30%) and colloid nodule (28.87%); the histopathological results were nodular hyperplasia (32.39%) and well differentiated papillary carcinoma (44.37%). 48.59% of patients showed postoperative complications being transient hypocalcemia (84.06%) and suffocating hematoma (2.90%) the most common in the first 24 hours and seroma in the first week (16.42%); there were no reported complications one month after surgery. According to the evidence, thyroidectomy performed without drainage is safe and does not increase postoperative complications at 24 hours, a week, or a month after surgery.
Keywords: thyroid pathology; drainage; thyroidectomy; complications